Sweetpotato support platforms to build a community of practice - International Potato Center (2013)
Key to building a community of practice is to participate in shared learning experiences. In August 2012, sweetpotato breeders from Africa and Asia learned modern molecular methods at a course hosted by the University of Ghent in Belgium. Back in SSA, SASHA conducted 9 three day in-country trainings on CloneSelector 3.0 and 12 SSA breeding programs shared their progress at the Speedbreeders annual meeting held in Kigali, Rwanda in April 2013.